2012
DOI: 10.4102/sajpsychiatry.v18i3.356
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among Grade 11 and 12 learners attending schools in central Bloemfontein

Abstract: <p><strong>Objectives.</strong> Anxiety disorders are the most common childhood psychiatric disorders. Previous research suggests that South African rates may be high. Our study examined the prevalence and severity of anxiety and depression among Grade 11 and 12 learners attending schools in central Bloemfontein. Learners’ perception of the important stressors as well as the most relevant coping strategies were investigated.<strong></strong></p><p><strong> Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Sixteen studies were carried out at sub-Saharan African research institutions [ 21 , 22 , 32 , 33 , 37 39 , 41 , 43 , 44 , 47 , 50 52 , 54 56 ] the majority in South Africa (n = 9). Nineteen of the studies were conducted in collaboration with researchers from HIC or other LMIC [ 13 , 22 30 , 35 , 36 , 40 , 43 , 48 , 49 , 53 , 55 , 57 ] and four studies were carried out by researchers based in HIC [ 34 , 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies were carried out at sub-Saharan African research institutions [ 21 , 22 , 32 , 33 , 37 39 , 41 , 43 , 44 , 47 , 50 52 , 54 56 ] the majority in South Africa (n = 9). Nineteen of the studies were conducted in collaboration with researchers from HIC or other LMIC [ 13 , 22 30 , 35 , 36 , 40 , 43 , 48 , 49 , 53 , 55 , 57 ] and four studies were carried out by researchers based in HIC [ 34 , 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve different screening tools and one clinical interview were used. As indicated in Fig 2 , the median point prevalence for depression across nine general population studies encompassing 14 409 adolescents [ 21 , 22 , 33 , 37 , 39 , 43 , 45 , 49 , 50 ] was 26.9% and the interquartile range (IQR) was 20.1–31.1 The median point prevalence for 11 studies (n = 12 614) with at-risk samples [ 25 28 , 30 , 35 , 36 , 38 , 48 , 52 , 53 ] was 29.0% (IQR 12.9–42.0) as shown in Fig 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In South Africa (SA), Kleintjes et al [8] reported that, although there were limited data on the prevalence of depression in SA adolescents, their study found that depression was one of the most common disorders reported in childhood and adolescence. Strydom et al [9] found that even though the prevalence of depression was not high in their sample, the depression rate was still higher in their adolescent sample compared with SA adult rates. Depression is a debilitating diagnosis and a subthreshold depression is known to affect quality of life.…”
Section: Articlementioning
confidence: 99%
“…Younger age groups of both genders are at higher risk, with female parasuicides being younger than males in many studies. [9] In SA age, race and city play independent roles in sex-specific suicide rates [10] and there is a need for specific research into suicide attempts in different SA cities. Despite some common trends across SA cities, there are variations in the magnitude and distribution of suicide mortality across race and sex groups and in the suicide method.…”
mentioning
confidence: 99%